Student Recruitment Management in Improving the Quality of Educational Institutions - Fitri, Fitri; Maharani, Silvia; Rahmawati, Rahmawati; Astuti, Astuti (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study explores the role of student recruitment management in enhancing the quality of educational institutions, with a case study conducted at SMP Negeri 4 Awangpone, Indonesia. Utilizing a qualitative descriptive approach, data were collected through structured interviews, observation, and documentation. The findings reveal that the recruitment process is systematically managed through four key phases: planning, organizing, implementation, and monitoring. The effectiveness of these processes significantly contributes to institutional improvement, particularly in student intake quality. Moreover, the study identifies several institutional quality drivers, including leadership commitment to quality, continuous teacher training, internal organizational support, effective communication, recognition and rewards, and routine evaluation practices. The results suggest that structured recruitment management not only streamlines student admission but also serves as a strategic tool to elevate educational quality. These findings have implications for school management practices in similar educational contexts.